CRITICAL THINKING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS IN GAME-BASED LEARNING USING GEMAS GAME - Nur Agustiani; Hamidah Suryani Lukman; Ana Setiani (Universitas Muhammadiyah Metro, 2024)
Games-based learning is a learning model that integrates material into games so that it can motivate students to think critically when solving problems. This study aims to review the critical thinking skills of junior high school students in learning mathematics that applies a game-based learning model using GEMAS game. This research uses the descriptive analysis method. The research was conducted at Tahfidz Quran Al-Fath Islamic Middle School with 29 students in class IX as research subjects; 2 subjects were taken to be interviewed about the results of their answers to the critical thinking ability test. Subjects were selected based on specific considerations, namely, students with high mathematical abilities and those with low mathematical abilities. Data collection was carried out using test and interview methods. Based on the analysis results, it was found that the percentage of students who could meet critical thinking according to FRISCO (Focus, Reason, Inference, Situasion, Clarity, dan Overview) criteria increased after game-based learning. There is an increase in critical thinking skills, both students with high mathematical abilities and those with low mathematical abilities. Students with high mathematical abilities have achieved better critical thinking criteria than students who have low mathematical abilities.   Pembelajaran berbasis games merupakan model pembelajaran yang mengintegrasikan materi ke dalam permainan (games) sehingga mampu memotivasi siswa untuk berpikir kritis dalam menyelesaikan masalah. Penelitian ini bertujuan untuk meninjau kemampuan berpikir kritis siswa SMP pada pembelajaran matematika yang menerapkan model pembelajaran berbasis game menggunakan game GEMAS.  Penelitian ini menggunakan metode analisis deskriptif. Penelitian dilakasanakan di SMP Islam Tahfidz Quran Al-Fath dengan subjek penelitian 29 siswa kelas IX, yang diambil 2 subjek untuk diwawancara mengenai hasil jawabannya terhadap tes kemampuan berpikir kritis. Subjek dipilih berdasarkan pertimbangan tertentu, yakni siswa yang memiliki kemampuan matematika tinggi dan siswa yang memiliki kemmapuan matematika kurang. Pengumpulan data dilakukan dengan metode tes dan wawancara. Berdasarkan pada hasil analisis, diperoleh persentase siswa yang mampu memenuhi kriteria berpikir kritis FRISCO (Focus, Reason, Inference, Situasion, Clarity, dan Overview) meningkat setelah pembelajaran berbasis game. Terdapat peningkatan kemampuan berpikir kritis, baik siswa dengan kemampuan matematika tinggi maupun siswa yang memiliki kemampuan matematika rendah. Siswa dengan kemampuan matematika tinggi memiliki ketercapaian kriteria berpikir kritis yang lebih baik dari siswa yang memiliki kemampuan matematika rendah.